D. I. ABRAMOVYCH’S COOPERATION WITH ALL-UKRAINIAN ACADEMY OF SCIENCES THROUGH THE PRISM OF EPISTOLARY DOCUMENTS - Andrii Shapoval (Київські історичні студії)
The article presents scientific cooperation of a literature and language historian, an archeographer and paleographer D. I. Abramovych with All-Ukrainian Academy of Sciences according to the analysis of the epistolary heritage of Ukrainian scientists. Epistolary documents of the Ukrainian scientists D. I. Abramorvych, V. M. Peretts, S. Yu. Gaievskyi, O. A. Nazarevskyi and K. V. Kharlampovych have become the source of the research that are stored in funds of the Institute of Manuscripts and the Institute of Archival Studies of the National Library of Ukraine named after V. I. Vernadsky. The special attention is paid to D. I. Abramovych’s activity in the Commission of Ancient Ukrainian Writing of the All-Ukrainian Academy of Sciences. Cooperation of the scientist with other institutions of All-Ukrainian Academy of Sciences, such as Society of Researchers of the Ukrainian History, Literature and Language in Leningrad, the Commission of All-Ukrainian Academy of Sciences for Drawing up the Biographic Dictionary of Figures of Ukraine, National Library of Ukraine is displayed. Letters open close professional cooperation of D. I. Abramovych with such outstanding Ukrainian scientists as V. M. Peretts, M. S. Grushevskyi, O. A. Nazarevsky, P. M. Popov, K. V. Kharlampovych. Activity of the Ukrainian scientists was directed to a research and the academic publication of works of ancient Ukrainian literature. Further studying of epistolary documents will allow to open more widely activity of the Ukrainian philologists in institutions of All-Ukrainian Academy of Sciences.